Small business management : - Megginson, Leon C. (McGraw - Hill / Irvin, 2006)
Operating any business is complex and challenging, but it provides interesting, creative, and rewarding experiences. Small Business Management, Fifth Edition, takes a practical and down-to-earth approach to planning, organizing, and running a small business. While employing current research and theory, Small Business Management takes a pragmatic "how-to" perspective illustrating many practical examples and applications from the business world. It explains how to achieve optimum benefits from the limited resources available to small firms, as well as how to plan for growth and succession in a business. It also explores arguments both for and against owning a small business. All three authors, Megginson, Byrd and Megginson, have had meaningful experiences in the "real world" as an owner, manager or employee of one or more small businesses.